Comprehensive Examination Performance and Work Performance - Castro, Rein Mark F.; Patricio, Noli B.; Tabamo, Ana Marie S. (Future Science / FSH-PH Publications, 2025)
The study employed a descriptive-correlational research design. Using the convenience sampling technique, the study obtained a total of 61 respondents from both MAEd and MBA graduates. Through the adoption of the questionnaire developed by Koopman (2014) entitled” Individual Work Performance Questionnaire (IWPQ) the study gathered necessary data. The study discovered that most of the respondents are Master of Arts in Education degree holders and currently occupying a position of Teacher III. Additionally, Graduates of MAEd and MBA obtained good performance in the Comprehensive Examination. Moreover, work performance of the Graduates in terms of contextual performance, adaptive performance and counterproductivity work behavior is excellent while very good in task performance. Lastly, the study revealed that there is no significant relationship between the comprehensive examination performance and work performance of the respondents. The study suggests to encourage ongoing education and professional development opportunities for Master of Arts in Education (MAEd) graduates, establish a peer tutoring or study group initiative within the MAEd and MBA programs, launch a recognition and rewards program within the organization, and undergo Continuing Professional Development (CPD) to maintain competence in their professional practice.